The effect of emigration on household labor supply: Evidence from Central Asia and South Caucasus - Saumik Paul (Asian Development Bank Institute (ADBI), 2018)
Using a novel data set, we find that households with migrants experience a 26% drop in the labor force participation rate in four economies (Armenia, Azerbaijan, the Kyrgyz Republic, and Tajikistan) from the Central Asia and South Caucasus region. It is twice as large for households with permanent migrants as for households with seasonal migrants. The results do not alter in the presence of selection on unobservables, model misspecification, and selection bias due to the absence of more productive workers. Direct evidence on the remittances that each household received is not available. The empirical findings do, however, suggest the possibility of an increase in reservation wages.
Keywords: F22; J61; 330; emigration; labor mobility